2022
DOI: 10.21037/atm-22-1148
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acid supplementation contributes to the amelioration of Alzheimer’s disease in mouse models

Abstract: Background: Alzheimer's disease (AD) is the most common cause of dementia. Effective therapy, early diagnosis, and intervention are still lacking. Non-drug therapy and lifestyle interventions have become important means to prevent the occurrence and progression of AD, with nutritional therapy being one such example. Nutritional therapy, as a non-pharmacological intervention for AD, has made significant progress and shown significant promise for the development of treatment regimens in recent years. Niacin is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Moreover, many biological targets and signaling pathways are involved in the pathology of dementia. There is substantial literature that focuses on drug targets for AD [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ], LBD [ 74 , 75 , 76 , 77 ], FTD [ 78 , 79 , 80 , 81 ], and VD [ 82 , 83 , 84 ]. As a result of a better understanding of the biochemical regulation of the mechanisms leading to dementia, new molecular targets have been introduced into clinical trials ( Table 3 ).…”
Section: Drug Discovery and Development For Dementiamentioning
confidence: 99%
“…Moreover, many biological targets and signaling pathways are involved in the pathology of dementia. There is substantial literature that focuses on drug targets for AD [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ], LBD [ 74 , 75 , 76 , 77 ], FTD [ 78 , 79 , 80 , 81 ], and VD [ 82 , 83 , 84 ]. As a result of a better understanding of the biochemical regulation of the mechanisms leading to dementia, new molecular targets have been introduced into clinical trials ( Table 3 ).…”
Section: Drug Discovery and Development For Dementiamentioning
confidence: 99%
“…Nicotinic acid is an indispensable vitamin in humans and animals. Li et al [32] found that nicotinic acid can enhance the cognitive ability of patients with Alzheimer's disease through a variety of mechanisms. In our study, nicotinic acid was significantly upregulated 2.18-fold after fermentation.…”
Section: Differential Alkaloid Compounds Before and After Fermentatio...mentioning
confidence: 99%
“…Thus, a biological link between niacin and cognition seems plausible. In addition, niacin is also beneficial in the prevention and treatment of aging, cancer, and metabolic diseases (Wang et al, 2022). A clinical study suggests that niacin supplementation has beneficial effects on cognitive function in later life (Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%